Participatory processes in public policies with a human rights approach - Iturralde Durán, Carlos (2023)
This article aims to reflect on the importance of participatory processes in public policies from the perspective of rights, using documentary and bibliographic research with a qualitative-descriptive approach, and conceiving policies as interventions carried out by governments to treat to change a reality towards another that has greater exercise of rights, and, therefore, that generates better levels of quality of life for the beneficiary agents. With three phases that comprise its cycle, public policies have an articulated technical structure, where design, management and evaluation are conceived as a single body, however, the factual application of ex post evaluation is little institutionalized. In each of them, the generation of participatory processes enhances their effectiveness, complementing technical knowledge with citizen knowledge and generating useful information for decision-making that improves the efficiency and effectiveness of public action, but also provides greater legitimacy and governance. while contributing to the expansion of freedoms and capabilities of the population, strengthening democracy; however, more appropriate mechanisms for its application must still be developed, in addition to an institutional culture with greater awareness of its benefits. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/2083